An Empirical Investigation of the Adjustment of Stock Prices to New Quarterly Earnings Information - Jordan, Ronald J. (Journal of Financial and Quantitative Analysis, 1973)
Ronald J. Jordan, An Empirical Investigation of the Adjustment of Stock Prices to New Quarterly Earnings Information, The Journal of Financial and Quantitative Analysis, Vol. 8, No. 4 (Sep., 1973), pp. 609-620